Molecular characterization, targeting and expression analysis of chloroplast and mitochondrion protein import components in Nicotiana benthamiana - Sáiz-Bonilla, María; Martín Merchán, Andrea; Pallás, Vicente; Navarro, Jose Antonio (Frontiers in Plant Science, 2022)
Improved bioinformatics tools for annotating gene function are becoming increasingly available, but such information must be considered theoretical until further experimental evidence proves it. In the work reported here, the genes for the main components of the translocons of the outer membrane of chloroplasts (Toc) and mitochondria (Tom), including preprotein receptors and protein-conducting channels of N. benthamiana, were identified. Sequence identity searches and phylogenetic relationships with functionally annotated sequences such as those of A. thaliana revealed that N. benthamiana orthologs mainly exist as recently duplicated loci. Only a Toc34 ortholog was found (NbToc34), while Toc159 receptor family was composed of four orthologs but somewhat different from those of A. thaliana. Except for NbToc90, the rest (NbToc120, NbToc159A and NbToc159B) had a molecular weight of about 150 kDa and an acidic domain similar in length. Only two orthologs of the Tom20 receptors, NbTom20-1 and NbTom20-2, were found. The number of the Toc and Tom receptor isoforms in N. benthamiana was comparable to that previously reported in tomato and what we found in BLAST searches in other species in the genera Nicotiana and Solanum. After cloning, the subcellular localization of N. benthamiana orthologs was studied, resulting to be identical to that of A. thaliana receptors. Phenotype analysis after silencing together with relative expression analysis in roots, stems and leaves revealed that, except for the Toc and Tom channel-forming components (NbToc75 and NbTom40) and NbToc34, functional redundancy could be observed either among Toc159 or mitochondrial receptors. Finally, heterodimer formation between NbToc34 and the NbToc159 family receptors was confirmed by two alternative techniques indicating that different Toc complexes could be assembled. Additional work needs to be addressed to know if this results in a functional specialization of each Toc complex.